2017
DOI: 10.5194/isprs-archives-xlii-4-w6-91-2017
|View full text |Cite
|
Sign up to set email alerts
|

Pixel-Based Classification Analysis of Land Use Land Cover Using Sentinel-2 and Landsat-8 Data

Abstract: ABSTRACT:The aim of this study is to conduct accuracy analyses of Land Use Land Cover (LULC) classifications derived from Sentinel-2 and Landsat-8 data, and to reveal which dataset present better accuracy results. Zonguldak city and its near surrounding was selected as study area for this case study. Sentinel-2 Multispectral Instrument (MSI) and Landsat-8 the Operational Land Imager (OLI) data, acquired on 6 April 2016 and 3 April 2016 respectively, were utilized as satellite imagery in the study. The RGB and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…Landsat-8 Operational Land Imager (OLI) data were acquired on 14 April 2013 for LULC classification and from November 2013 to May 2014 for LST retrieval, respectively (https://earthexplorer.usgs.gov/). Landsat images are constantly improving by the richness in spectral, spatial, radiometric, and temporal resolution [54] with the new generations of satellites with improved sensors. The Operational Land Imager (OLI) and Thermal Infrared Sensor (TIRS) are instruments onboard the Landsat-8 satellite, which was launched in February 2013.…”
Section: Landsat-8 Oli/tirsmentioning
confidence: 99%
“…Landsat-8 Operational Land Imager (OLI) data were acquired on 14 April 2013 for LULC classification and from November 2013 to May 2014 for LST retrieval, respectively (https://earthexplorer.usgs.gov/). Landsat images are constantly improving by the richness in spectral, spatial, radiometric, and temporal resolution [54] with the new generations of satellites with improved sensors. The Operational Land Imager (OLI) and Thermal Infrared Sensor (TIRS) are instruments onboard the Landsat-8 satellite, which was launched in February 2013.…”
Section: Landsat-8 Oli/tirsmentioning
confidence: 99%
“…The results of the Sentinel-2 images' classification in the study were satisfactory, indicating that it is reasonable to automate the process of the classification of land cover and for monitoring the increase in forested areas. According to papers using Sentinel images [31][32][33][34] and preparing terrain information for reclaimed areas using remote sensing data [7][8][9][65][66][67][68][69], research has confirmed the possibility of using Sentinel-2 images for LULC change detection and for the monitoring of vegetated areas in reclaimed areas.…”
Section: Discussionmentioning
confidence: 99%
“…The process of land cover mapping, especially in terms of reclaimed areas, is the subject Sentinel-2 satellite imageries (European Space Agency; ESA) consist of two satellites: Sentinel-2A (launched in 2015) and Sentinel-2B (launched in 2017). The satellites are equipped with modern multi-spectral high-resolution scanners − 13 spectral channels with spatial resolution of 10, 20, and 60 m. Using Sentinel-2 (ESA) imageries opens up new possibilities in environmental studies [11,[31][32][33][34], mainly as a result of the good spatial and spectral resolution and short revisit time (five days for two satellites).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of Sentinel-2 spectral bands in land-use classification (Gašparović & Jogun, 2017;Georgescu, Vaduva & Datcu, 2017;Sekertekin, Marangoz & Akein, 2017). Most have found that the Vegetation Red Edge bands are helpful in discriminating between vegetation types (Delegido, Verrelst, Alonso & Moreno, 2011;Immitzer, Vuolo & Atzberger, 2016).…”
Section: Input Featuresmentioning
confidence: 99%